Water Physicochemical Impacts of Sidoarjo Mud Reservoir on Metal Degradation and Environmental Risks - Rohimatush Shofiyah; Yuvita Dian Siswanti; Senki Desta Galuh; Sevira Ayu Andini; Nur Hafifah (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Environmental monitoring in the Lapindo mudflow area has primarily focused on pollution assessment, with limited attention to the relationship between extreme water quality conditions and the corrosive environment affecting metallic infrastructure. This study evaluated physicochemical water quality in the Porong River mud reservoir to assess its potential influence on metal degradation. Water samples were collected in triplicate from eight strategically selected sites using stratified random sampling and analyzed using standard physicochemical methods. Severe spatial variations were observed, with Total Suspended Solids reaching 98,910 mg/L, dissolved oxygen depleted to 0.0 mg/L, and Chemical Oxygen Demand peaking at 4,182 mg/L, indicating highly polluted and anoxic conditions. The combination of elevated suspended solids, organic pollutants, and oxygen depletion creates an aggressive electrolytic environment that may accelerate corrosion processes. These findings provide new insights into corrosion-related environmental conditions in mud-volcanic aquatic systems and support environmental monitoring and infrastructure management in long-term mudflow-affected areas.